2009
DOI: 10.1068/p6317
|View full text |Cite
|
Sign up to set email alerts
|

Don't Stand So Close to Me: The Effect of Auditory Input on Interpersonal Space

Abstract: We provide preliminary evidence that listening to music through headphones alters the perception of space around the body -- specifically, the interpersonal distance maintained between the self and others. In comparison to an external auditory environment, wearing headphones or earplugs increased the amount of space maintained between the wearer and another person during an active approach paradigm. This finding suggests that, when external cues to spatial location (such as sound) are removed, people compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…It has been reported that listening to news through headphones (versus loudspeakers) seems to shorten the interpersonal distance between the listener and the news anchor, thus providing a more intense, arousing and pleasant experience [41]. Our findings also extend the study by Lloyd et al [22] on the effect of different auditory input on interpersonal distance by linking changes in the interpersonal behavior of participants with differences on emotional state. In that study, an increase in preferred interpersonal distance during approach-distance tasks when wearing earplugs or headphones with music, as compared to the open ears condition, was found.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has been reported that listening to news through headphones (versus loudspeakers) seems to shorten the interpersonal distance between the listener and the news anchor, thus providing a more intense, arousing and pleasant experience [41]. Our findings also extend the study by Lloyd et al [22] on the effect of different auditory input on interpersonal distance by linking changes in the interpersonal behavior of participants with differences on emotional state. In that study, an increase in preferred interpersonal distance during approach-distance tasks when wearing earplugs or headphones with music, as compared to the open ears condition, was found.…”
Section: Discussionsupporting
confidence: 86%
“…One of the five possible music tracks was played and the participant listened to it until a short beep occurred, at approximately 12 s after the onset of the music track. This beep signaled the start for the participant to walk towards the Experimenter A (approach-distance task; see [22]), or for Experimenter A to walk towards the participant (stop-distance task; see [2]). The participants' task, which was indicated to them at the beginning of each block and trial, was to stop walking (in the approach-distance task) or to say “stop” (in the stop-distance task) when they began to feel uncomfortable with the distance between them and the experimenter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to cope with these situations, individuals employ strategies to feel more comfortable when confronted with the uneasiness of a personal space invasion. On public transport, such strategies might involve engaging in activities such as reading, playing with smartphones or listening to music over headphones (Evans and Wener, 2007;Hirsch and Thompson, 2011;Lloyd et al, 2009;Tajadura-Jiménez et al, 2011). A common strategy to deal with social proximity is therefore to withdraw attention to the wider outside environment and retreat into an attentional space confined to peripersonal space.…”
Section: Introductionmentioning
confidence: 98%
“…For example, PPS can be extended through tool-use (68), by satisfying social interaction with others allowing integrating them to one’s PPS (9) or by depriving individuals of auditory cues from the external world (10). PPS can also be shrunk by increasing the effort needed to perform a hand movement with wrist weights (11) or by listening to positive emotion-inducing music through headphones leading to a better tolerance of others’ proximity (12).…”
Section: Introductionmentioning
confidence: 99%